Representasi Realitas Dunia Pop Art Warhol Sebuah Tinjauan Semiologi - Baskoro Suryo Banindro (DeKaVe, 2019)
Abstract.This study is the result of a pre-discussion on the meaning of Andy Warhol's printmaking object material. The purpose of this study is to obtain an outline of the description of the reality and myths in Warhol's work. Data is obtained from visual objects in the field and relevant literature studies, then descriptively will be analyzed by Danesi, semiological approach. The results of this study concluded that through printmaking's pop art work, Warhol wanted to build an ideology perpetuated by the dominant forces in society.Keywords:Warhol, pop art graphic art, ideology